PENERAPAN MEDIA PEMBELAJARAN MELALUI MEDIA DISPLAY UNTUK MENINGKATKAN HASIL BELAJAR SISWA PADA MATA PELAJARAN PPKN KEANEKARAGAMAN SUKU BANGSA KELAS 4 DI SEKOLAH DASAR - Nurhasanah, Ana; Adya Pribadi, Reksa; Wulandari, Sindy (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2021)
Learning media is a tool that is used as a support for the implementation of learning to learn to learn to learn, ranging from book sources to other media, and researchers also provide learning media in the form of display board media to 4th grade students in SDN Panunggulan 2 as a learning media tool so that learning can run effectively. The display media itself is a medium that can be used to display images such as posters, and other small objects that are three-dimensional with this also as a support for student learning so that students can be used in learning and also seen directly by students. Therefore, researchers provided a media display in the form of this image to the 4th class on the material of ethnic diversity in Indonesia because in the material is still low learning results about VAT material diversity of ethnic groups in Indonesia and.the use of this media aims to help teachers and students in improving learning outcomes. Learning outcomes are changes in students including their behavior in real terms that are done through the teaching and learning process that is in accordance with the learning objectives and with the learning outcomes teachers are able to see the development that has been owned by the student.